2021
DOI: 10.1111/1756-185x.14042
|View full text |Cite
|
Sign up to set email alerts
|

Large fiber peripheral neuropathy in systemic sclerosis: A prospective study using clinical and electrophysiological definition

Abstract: Aim The reported prevalence of peripheral neuropathy in systemic sclerosis (SSc) is variable between 0.01% to 28%, probably due to differences in sample size, study design and population. Our aim is to determine the prevalence of large fiber peripheral neuropathy in SSc and to identify any contributing factors. Method A prospective cross‐sectional study of 60 SSc patients were evaluated for large fiber neuropathy using the modified clinical Total Neuropathy Score (cTNS) and nerve conduction study (NCS) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…There were 39 patients with a limited disease form in our study, while diffuse disease was found in 17 patients. Raja et al (42) determined the prevalence of large fiber peripheral neuropathy in the group of 60 patients diagnosed with SSc and their results showed that 22 patients (36,7%) had peripheral neuropathy, which is in correlation with the results of our study. Since in the studied population axonal neuropathy was seen at a higher percentage, for which low amplitudes were specific electrophysiologically, our aim was to investigate the measure of the impact of disease activity and disease duration on the reduction of amplitude since it was the most important parameter in the initial neuropathy stages in autoimmune diseases.…”
Section: Discussionsupporting
confidence: 91%
“…There were 39 patients with a limited disease form in our study, while diffuse disease was found in 17 patients. Raja et al (42) determined the prevalence of large fiber peripheral neuropathy in the group of 60 patients diagnosed with SSc and their results showed that 22 patients (36,7%) had peripheral neuropathy, which is in correlation with the results of our study. Since in the studied population axonal neuropathy was seen at a higher percentage, for which low amplitudes were specific electrophysiologically, our aim was to investigate the measure of the impact of disease activity and disease duration on the reduction of amplitude since it was the most important parameter in the initial neuropathy stages in autoimmune diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Nerve conduction studies (NCS) are the gold standard exam for diagnosing DPN [ 119 ]. NCS allows an evaluation of the large fibers (myelinated alpha and beta), while with this tool it is not possible to identify the function of the small fibers (small myelinated Aδ-fibers and unmyelinated C-fibers) [ 120 , 121 ]. The application of skin electrodes permits nerve stimulation in μV and the detection of electrical nerve activity through a series of parameters that are useful for diagnosing nerve and muscle fiber pathologies [ 120 , 122 , 123 , 124 , 125 ].…”
Section: Diagnosismentioning
confidence: 99%
“…In fact, there are studies that identify dcSSc and anti-centromere positivity as major risk factors for peripheral neuropathy [4,30], whereas others found a significant association with lcSSc and positivity for anti-topoisomerase I and anti-U1-RNP [9,31]. Although, there are also studies that have not highlighted a particular influence of cutaneous involvement or autoantibody profile [6,32]. In this regard, larger cohort, multicentre studies are needed to confirm association with specific diseae characteristics.…”
Section: Discussionmentioning
confidence: 99%